2021
DOI: 10.1038/s41598-021-82482-z
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis cum machine learning approaches address the structure and biogeochemical potential of marine copepod associated bacteriobiomes

Abstract: Copepods are the dominant members of the zooplankton community and the most abundant form of life. It is imperative to obtain insights into the copepod-associated bacteriobiomes (CAB) in order to identify specific bacterial taxa associated within a copepod, and to understand how they vary between different copepods. Analysing the potential genes within the CAB may reveal their intrinsic role in biogeochemical cycles. For this, machine-learning models and PICRUSt2 analysis were deployed to analyse 16S rDNA gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 78 publications
(117 reference statements)
1
22
0
Order By: Relevance
“…C. ponticus showed several interactions with both clusters, suggesting that the ability to switch between filter and ambush feeding behavior (Benedetti et al, 2016) might allow this species to harbor a more diverse microbial community. Thus, feeding strategy may shape the copepod microbiota, as has been suggested in previous studies (De Corte et al, 2018;Sadaiappan et al, 2021;Tang et al, 2010). nana are omnivores, targeting a variety of prey types (phytoplankton, detritus, or smaller zooplankton) (Benedetti et al, 2016) while…”
Section: Main Drivers Of the Copepod Microbial Compositionmentioning
confidence: 74%
See 3 more Smart Citations
“…C. ponticus showed several interactions with both clusters, suggesting that the ability to switch between filter and ambush feeding behavior (Benedetti et al, 2016) might allow this species to harbor a more diverse microbial community. Thus, feeding strategy may shape the copepod microbiota, as has been suggested in previous studies (De Corte et al, 2018;Sadaiappan et al, 2021;Tang et al, 2010). nana are omnivores, targeting a variety of prey types (phytoplankton, detritus, or smaller zooplankton) (Benedetti et al, 2016) while…”
Section: Main Drivers Of the Copepod Microbial Compositionmentioning
confidence: 74%
“…Based on the assumption that microbial composition might reflect the host dietary preferences and feeding behavior, it is possible to assume that Calanus and Pleuromamma would display low microbial diversity as does Temora. However, Sadaiappan et al (2021) showed that Calanus and Pleuromamma exhibited more diverse microbial communities than Temora, suggesting that other ecological traits such as diel vertical migration may be contributing to the microbial compositional variation of the copepods. While…”
Section: Main Drivers Of the Copepod Microbial Compositionmentioning
confidence: 97%
See 2 more Smart Citations
“…Read pairs were merged and dereplicated and chimera removed with the “pooled” setting using DADA2 ( 52 ). Taxonomic assignments for the resulting amplicon sequencing variants (ASVs) used a pretrained naive Bayes classifier on the full-length 16S rRNA genes in the SILVA 138 SSURef NR99 database ( 53 , 54 ). ASVs assigned to the same level 7 taxonomy were combined, and those assigned to mitochondria or chloroplast or without taxonomy assignments were removed using the –p-exclude mitochondria,chloroplast,“Bacteria;Other;Other;Other;Other;Other,”“Unassigned;Other;Other;Other;Other;Other” setting.…”
Section: Methodsmentioning
confidence: 99%